Effectiveness of Hydrilla verticillata (L.F.) Royle as a phytoremediation agent in Kaligarang River raw water - Achmad, Chusnul Adib; Lestari, Yunita Dwi; Purnomo, Eko (Journal of Natural Sciences and Mathematics Research, 2024)
The main source of pollutants is the impact of domestic (household waste), which pile up due to high population levels. The accumulation of domestic waste produces wastewater containing heavy metals, including iron (Fe), which is then absorbed into the ground and flows into rivers. Phytoremediation is a method that can remove, absorb, destroy, and degrade pollutants, including heavy metals, in water. Hydrilla verticillata (L.f.) Royle has become a plant known as a good phytoremediator agent. This research aims to determine morphological changes and the effect of phytoremediation Hydrilla verticillata (L.f.) Royle will remediate the water of the Kaligarang River with an exposure time of 5 and 10 days. The testing of iron level (Fe) is done using analysis with atomic absorption spectroscopy (AAS). The results obtained were that the iron (Fe) content was originally 1.2222 mg/L, decreased as much as 0.9539 mg/L in treatment S1 with an average value of 0.1683 mg/L, and in treatment S2 decreased to 0.3557 mg/L with an average value of 0.766.